Factores determinantes de la entrada de IED en 8 economías latinoamericanas (2004-2018) – enfoque empresas multinacionales - Aponte Laos, Dinora Paloma (2021)
This working paper’s purpose is to analyze the impact of the most relevant factors for Foreign Direct Investment (FDI) inflows in the 8 Latin American economies (Pacific Alliance, Argentina, Brazil, Bolivia and Ecuador) in the period 2004 – 2018, considering the presence of multinational enterprises (MNE). According to the results, the tax payment, different to what was expected, had a positive impact on FDI inflows, which it’s also convenient for MNEs; the variable “exports” as well, turned to be a positive determinant for FDI inflows in these economies, in addition, exports are attractive for MNEs since it would allow them to trade resources efficiently; moreover, the total income from natural resources had a positive effect on FDI inflows, this outcome is important due to it is a common characteristic shared by all these economies, which incentive MNEs presence in them. On the other hand, we evaluated several kinds of policies used in order to attract more foreign investment, in line with that, we reviewed not only the cases of each country studied in this working paper, but also successful cases of other countries. So, we could recommend that these economies should have localization strategies, define priorities, evaluate internal and external factors of the country and stablish offices so they can promote their country’s attractiveness. Likewise, it was concluded that for Peruvian case, it is necessary to thoroughly analyze its strengths and weaknesses; the establishment of regular meetings is also suggested in order to discuss the current context of trade and competitiveness, and should also increase the number of double taxation agreements.